Early Neurodevelopmental Outcomes after Previable Preterm Prelabour Rupture of Membranes (pPPROM). (20th September 2022) - Pylypjuk, Christy L.; Nikel, Katarina; Day, Chelsea; Majeau, Ladonna; Yu, Adelicia; ElSalakawy, Yasmine; Ricci, M. Florencia
Abstract : Objective . To describe the early neurodevelopmental outcomes following fetal exposure to previable preterm prelabour rupture of membranes (pPPROM). Methods . This was a secondary analysis of a subgroup of neonates born following pPPROM from a retrospective cohort study (2009–2015). Surviving infants who underwent standardized neurodevelopmental evaluation at 18–24 months corrected age (CA) between 2017 and 2019 were eligible for inclusion. Data abstracted from hospital charts were linked to prospectively collected developmental outcomes stored in an electronic database from a regional neonatal follow-up clinic. The primary outcome was Bayley-III composite scores (compared to the population mean 100, standard deviation (SD) 15). Secondary outcomes included presence of cerebral palsy, vision loss, hearing impairment, and requirement of rehabilitation therapy. Descriptive statistics were used to present results. Results . 25.7% (19/74) of neonates born after pPPROM survived to hospital discharge, but only 21.6% (16/74) survived to 18–24 months CA. Of these, 9 infants were eligible for follow-up at the regional clinic and 7 had developmental outcomes stored in the electronic database. Infants exposed to pPPROM exhibited Bayley-III scores more than 1 SD below the population mean across all three domains: cognitive 84.9 (SD 12.2); motor 82.3 (SD 11.5); and language 66.4 (SD 18.9). There were particular deficiencies in language development with 71% (5/7) scoring more than 2 SDs below the population mean. There were no cases of cerebral palsy. Conclusions . Only 1 in 5 infants born following expectantly managed pPPROM survived to 18–24 months CA. These infants born after pPPROM had significantly lower Bayley-III scores and particular deficiencies in language development. Better understanding of early neurodevelopmental challenges following pPPROM will help refine counselling of families contemplating expectant management and provide insights into the postnatal educational resources required to improve long-term developmental outcomes for these children.